A Fatal Herpes Simplex Encephalitis with a Normocellular Cerebrospinal Fluid: A Case Report - Karolina Dutkowska; Krystian Ejdys; Marcin P. Mycko (Journal of Clinical Medicine, 2026)
Background: Herpes simplex encephalitis (HSE) is a rare but life-threatening infection of the central nervous system associated with high mortality and severe neurological sequelae. The diagnosis may be particularly challenging in patients presenting with atypical clinical or laboratory findings. Case presentation: An 85-year-old woman presented with progressive impairment of consciousness and generalized neurological deterioration. Initial neuroimaging suggested an acute ischemic stroke, whereas subsequent brain magnetic resonance imaging (MRI) demonstrated bilateral temporal and insular cortical abnormalities suggestive of encephalitis. Cerebrospinal fluid (CSF) analysis revealed no pleocytosis, and blood tests showed no markers of systemic inflammation during admission, which initially lowered the suspicion of infectious encephalitis. Although no inflammatory cells were detected in the routine CSF examination, polymerase chain reaction (PCR) testing confirmed infection with herpes simplex virus type 1 (HSV-1). Despite the prompt initiation of acyclovir after suspicion of encephalitis with MRI, together with corticosteroid therapy, anticonvulsants, and supportive treatment, the clinical course was fatal. Conclusions: This case highlights the diagnostic challenges associated with HSE, particularly in patients with normocellular CSF and radiological findings that may mimic other neurological conditions, including ischemic stroke. The absence of CSF pleocytosis does not exclude HSE, although the timing of CSF sampling should be considered when interpreting this finding. Early MRI and molecular CSF diagnostics remain essential for establishing an accurate diagnosis and ensuring timely treatment.